Egyptian Centres and the Distribution of the Alphabet in the Levant. (2nd January 2020) - Na'aman, Nadav
Abstract : The article contends that the adoption of the alphabetic script in the Levant in the LB II–early Iron Age is best explained by the scribal activity of the Empire's representatives in the Egyptian centres of government and by the display of artefacts written in the hieroglyphic script in these centres. The early alphabetic inscriptions clustered mainly in regions located near the Egyptian centres of Gaza, Joppa, Beth-shean and Kumidi and the city-states of Lachish and Byblos. The latter was the first city that developed extensive writing in the alphabetic script and the first to form a scribal school under the patronage of its royal court. Although the Egyptian display inscriptions and scribal culture inspired the local Canaanite elites, the latter, rather than adopting the prestigious Egyptian script and language, absorbed only the idea of writing, and applied it to their culture in the revolutionary medium invented hundreds of years earlier in the Sinai Peninsula.